1991
DOI: 10.1029/91wr01095
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction of Electrical Conductivity in Saturated and Unsaturated Soil

Abstract: A conceptual model is proposed for the prediction of the electrical conductivity of bulk soil in saturated and in unsaturated states. The model is based on the hypothesis that the tortuosity factor affecting the bulk soil electrical conductivity is identical to that defined for prediction of the soil hydraulic conductivity. Simple mathematical functions are derived to forecast the soil electrical conductivity as a function of the water content. Experimental results of seven previous studies carried out on 26 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
155
0
7

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(165 citation statements)
references
References 17 publications
(2 reference statements)
3
155
0
7
Order By: Relevance
“…As for the K a -Q w relationship, several types of models have been proposed for the relationship between a a , a w and 0 W , e.g. purely empirical models (Persson, 1997), empirical-conceptual models (Mualem & Friedman, 1991), and physical-conceptual models (Rhoades et al, 1976;Rhoades et al, 1989). However, it is important to note that all these models have serious drawbacks in that, for example, they need to be calibrated for each soil type and are only applicable for a specific range in Q w and a w .…”
Section: Open For Discussion Until 1 December 2001mentioning
confidence: 99%
See 2 more Smart Citations
“…As for the K a -Q w relationship, several types of models have been proposed for the relationship between a a , a w and 0 W , e.g. purely empirical models (Persson, 1997), empirical-conceptual models (Mualem & Friedman, 1991), and physical-conceptual models (Rhoades et al, 1976;Rhoades et al, 1989). However, it is important to note that all these models have serious drawbacks in that, for example, they need to be calibrated for each soil type and are only applicable for a specific range in Q w and a w .…”
Section: Open For Discussion Until 1 December 2001mentioning
confidence: 99%
“…Risler et al (1996) found that a constant transmission coefficient in equation (4) was adequate to model the a a vs o" w -9 w relationship using their data at low a a values (2-4 dS m" 1 ). Mualem & Friedman (1991) had a slightly different approach using the tortuosity factor F ê (Q w ) instead of the transmission coefficient to account for the complex geometry of the soil matrix. They proposed that F g should be equal to the ratio of the hydraulic conductivity of the soil to that of a bundle of straight capillaries.…”
Section: Models For the O Fl Vs A W -Q W Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of these comments is to provide a further test of the models presented by Mualem and Friedman [1991] using measurement data for Ottawa sands reported by Gorman [1989] and Gorman and Kelly [1990].…”
mentioning
confidence: 99%
“…As Mualem and Friedman [1991] imply, a general problem with electrical measurement procedures is that they are not standardized and thus key parameters for comparisons and testing of theoretical models are frequently missing.…”
mentioning
confidence: 99%